Cultura de segurança de alimentos – ISO 22000: um estudo de caso em empresa do Polo Industrial de Manaus no ramo de embalagens de alimentos - Catão, Leticia Brito (Brasil, 2024)
This study focuses on the strategies for implementing Food Safety Culture, with a case study in a company from the industrial hub of Manaus, operating in the food packaging sector. The primary objective was to analyze practices perceived by employees of the Food Safety Culture. The research employed an exploratory-descriptive method, aiming to describe the characteristics of the established safety culture and provide a detailed understanding of the implementation process. A formative evaluation approach was applied to offer continuous feedback and assess the maturity of the culture, with the goal of improving internal processes. The SWOT analysis tool identified the strengths, weaknesses, opportunities, and threats related to the company's current scenario. The results highlighted strong points, such as structured internal communication and positive leadership influence, while weaknesses included challenges in adherence within support areas and inconsistencies among departments. Based on the insights gathered, recommendations were proposed to strengthen the safety culture, enhance protocol compliance, and consolidate a more preventive and integrated approach.